Sistem Pendukung Keputusan Kelayakan Penerimaan Bantuan Pinjaman Modal Usaha Kecil Menengah Dengan Metode Smart - Lutfi Singgih Pangestu; Yusriel Ardian; Wiwin Kuswinardi (RAINSTEK : Jurnal Terapan Sains & Teknologi, 2019)
Admission eligibility decision support systems help small and medium enterprises loan capital was built for the village BUMDes Slorok in determining who is eligible to receive assistance capital loans. In the process for the selection of beneficiaries of loans has a lot of requirements or criteria which are ID cards, Letter of approval husband / wife, status, number of families, home ownership, income, dependents of school children, old business, assets owned. In this study the feasibility of beneficiary selection process will be conducted by the method Simple Multi Attribute Rating Technique (SMART) Is a multi criteria decision making methods. The research model development using the Waterfall model. The results can be concluded from this study, the value obtained by each candidate receiving debt relief will dinputkan to this decision support system and be counted. Then displays the calculation results based on the rank ordering of where the highest score will be on top.